Relationships between leaf morphological traits, nutrient concentrations and isotopic signatures for Mediterranean woody plant species and communities - Domínguez, María T.; Aponte, Cristina; Pérez-Ramos, Ignacio M.; García, Luis V.; Villar, Rafael; Marañón, Teodoro (Plant and Soil, 2012)
Background and aims Soil factors are driving forces that influence spatial distribution and functional traits of plant species. We test whether two anchor morphological traits—leaf mass per area (LMA) and leaf dry matter content (LDMC)—are significantly related to a broad range of leaf nutrient concentrations in Mediterranean woody plant species. We also explore the main environmental filters (light availability, soil moisture and soil nutrients) that determine the patterns of these functional traits in a forest stand. Methods Four morphological and 19 chemical leaf traits (macronutrients and trace elements and δ 13 C and δ 15 N signatures) were analysed in 17 woody plant species. Community-weighted leaf traits were calculated for 57 plots within the forest. Links between LMA, LDMC and other leaf traits were analysed at the species and the community level using standardised major axis (SMA) regressions Results LMA and LDMC were significantly related to many leaf nutrient concentrations, but only when using abundance-weighted values at community level. Among-traits links were much weaker for the crossspecies analysis. Nitrogen isotopic signatures were useful to understand different resource-use strategies. Community-weighted LMA and LDMC were negatively related to light availability, contrary to what was expected. Conclusion Community leaf traits have parallel shifts along the environmental factors that determine the community assembly, even though they are weakly related across individual taxa. Light availability is the main environmental factor determining this convergence of the community leaf traits.
Keywords: Community weighted means; functional traits; isotopes; leaf dry matter content; Leaf mass per area; macronutrients; Specific leaf area